Persepsi dan Partisipasi Masyarakat terhadap Penggunaan Tipe-tipe Lahan di Lansekap Tahura Bukit Barisan (Studi Kasus: Desa Surbakti dan Desa Beganding, Kecamatan Simpang Empat, Kabupaten Karo) - Trigustien Sinambela; Oding Affandi; Liliek P. Asmono (Program studi Kehutanan USU, 2013)
This research conducted in Surbakti and Beganding village, Simpang Empat Sub district, Karo District, in May ‘till July 2012. The aim of this research was to study community perseption and urgention of the land use as forest and it’s benefit compared with other land use in Bukit Barisan Forest Park, and to examin community participation about forest developing effort. Method of the research used MLA ((Multidisciplinary Landscape Assesment) method. These method was skoringr with Focus Group Discussion (FGD) that use Pebble Distribution Method (PDM). Respondents on household survey was 60 head of family from two village, traditional leader, head of village and key information person. Keyword : Community Perception, Community Participation, MLA Method, Bukit Barisan Forest Park.